Pengaruh Harga, Lokasi dan Fasilitas Terhadap Keputusan Berkunjung (Studi Pada Pengunjung Tempat Wisata Bale Tani) - Sibro Amrizi; Tri Sudarwanto (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2021)
Bale tani tourist attraction has approximately 130 visitors per day on holidays the number of visitors can reach approximately 200 visitors every day.The population in this study were all tourist visitors at the Bale Tani Jombang tourist attraction. The sample was determined by accidental sampling technique, the sample size was determined based on the Sugiono formula obtained by 52 respondents. Data collection methods used questionnaires and documentation.The conclusion from this research is that it can be seen that the value of the R Square adjuster = 0.642, it can be said that the change in variable Y (the decision to visit) is 64.2% due to the variable price, location and facilities, while the remaining 35.8% is caused by other factors outside these variables. The suggestion that can be given is that Bale Tani Jombang can provide a policy for price adjustments so that visitors can enjoy existing facilities, Bale Tani Jombang also does not have public facilities such as an ATM machine and inadequate access to the tourist attraction Bale Tani Jombang.Keywords: Price; Location; Facilities; Visitor Decisions